IMPACT OF RHIZOSPHERE ANTAGONISTIC BACTERIA AND UREA FERTILIZER ON ROOT KNOT NEMATODE (MELOIDOGYNEINCOGNITA) UNDER GREEN HOUSE CONDITION - S. Ketabchi; H. Charehgani; S. Majzoob (Journal of Animal and Plant Sciences, 2016)
The effect of rhizosphere bacteria on activity of root-knot nematode (Meloidogyne incognita) was investigated under laboratory and greenhouse conditions. Rhizosphere bacteria were isolated from roots of plants infected with root knot nematode. The effect of the rhizosphere bacteria on second stage juvenile mortality of M. incognita under laboratory conditions was studied after 24, 48 and 72 hs. Three bacterial isolates, Serratia sp., Pseudomonas fluorescensCHA0, and Pseudomonas putida, that caused the higher mortality of second stage juvenile, were used in greenhouse experiment. They were evaluated with and without application of 50 mg urea fertilizer per kg of soil, on tomato (Solanumly copersicum) infected with M. incognita. All treatments had positive effect on plant growth parameters, and decreased the nematode-related parameters, such as number of gall, egg and egg mass, as well as the reproduction factor. Moreover, application of Serratia sp. in combination with urea fertilizer had the greatest effect, as compared to other treatments. The experiments were repeated and similar results were obtained.
Keywords: Nitrogen; Pseudomonas fluorescens CHA0; Pseudomonas putida; Tomato; Serratia sp